Deposits as a Tool for Effective Income Management: Evidence from Nepal - Sunar, Upendra (KVM Research Journal, 2025)
Deposits are among the most fundamental tools of financial management, offering safety, liquidity, and discipline to households while providing the foundation of liquidity for banks. In Nepal, where inflation, irregular income, and low financial literacy remain widespread, the role of deposits in income management is both critical and contested. This study adopts a mixed-methods approach, combining a nationwide survey of 250 respondents across all seven provinces with 20 qualitative interviews in Mahendranagar, Kanchanpur. Quantitative results indicate that income, financial literacy, and digital banking adoption are the strongest predictors of consistent deposit behavior, explaining nearly half of the variance in saving regularity. Qualitative findings reveal cultural reliance on cash, distrust in cooperatives, and digital divides that limit deposit adoption in rural areas. The study concludes that while deposits are effective in enhancing financial discipline and household stability, structural barriers such as inflation and behavioral constraints such as low awareness must be addressed. It recommends financial literacy campaigns, inflation-protected deposit schemes, and inclusive digital banking solutions as key strategies to strengthen deposit utilization in Nepal.